HIGH SCHOOL ZONING POLICY IMPACT ON TRANSPORTATION IN BANDUNG CITY WEST JAWA PROVINCE - Miming Miharja; Anindita Putri Dewanti; Renny Desiana (Jurnal Ilmu Pemerintahan Widya Praja, 2022)
The enactment of the zoning policy through the Minister of Education and Culture Regulation (Number 14/2018) concerning the Admission of New Students states that the admission priority would be given to those who live within the radius of the closest zone from the school. From a transportation perspective, this policy has a potential positive impact in creating a more balanced school trip distribution pattern, and would further reduce the total trip length and improve transportation performance. Taking Bandung City as a case, this study aims to evaluate the impact of the Penerimaan Peserta Didik Baru/PPDB (New Student Admission) based on zoning system policy on the travel distribution patterns of high school students in this city. The method used in this research is spatial distribution analysis and qualitative descriptive analysis. The research performs a before-after analysis of comparison to analyze the impact of the policy on schooling trip distribution. The results show that the zoning policy stimulates the total change of the average schooling trip length of high school students in Bandung by 35%. This research also concludes that the schooling trip distribution pattern is no longer centered in the city center where favorite schools were located. Keywords: Government Policy, School Zoning, Bandung City Transportation.